Shortened therapy of eight weeks with paritaprevir/ritonavir/ombitasvir and dasabuvir is highly effective in people with recent HCV genotype 1 infection. Issue 10 (8th May 2018) - Martinello, M.; Bhagani, S.; Gane, E.; Orkin, C.; Cooke, G.; Dore, G. J.; Petoumenos, K.; Applegate, T. L.; Tu, E.; Marks, P.; Pagani, N.; Grebely, J.; et al.
Summary: Paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for 12 weeks are approved for treatment of chronic HCV genotype 1 infection. This study assessed the efficacy of shortened duration paritaprevir/ritonavir/ombitasvir and dasabuvir with or without ribavirin for 8 weeks among people with recent HCV infection. In this open‐label single‐arm trial conducted in Australia, England and New Zealand, adults with recent HCV (duration of infection <12 months) received paritaprevir/ritonavir/ombitasvir and dasabuvir (with weight‐based ribavirin for genotypes 1a and 1, no subtype) for 8 weeks. The primary endpoint was sustained virological response at 12 weeks post‐treatment (SVR12) in the intention‐to‐treat (ITT) population. Thirty people (median age 38 years, male 93%) commenced treatment (with ribavirin, 97%), of whom 77% (n = 23) were HIV‐positive, 93% (n = 28) had genotype 1a infection and 53% (n = 16) had ever injected drugs. Median maximum ALT in the preceding 12 months was 433 IU/L (IQR 321, 1012). Acute clinical hepatitis with ALT > 10 x ULN was documented in 83% (n = 25); one participant (3%) had jaundice. At baseline, median estimated duration of infection was 30 weeks (range 11, 51), and median HCV RNA was 5.7 log10 IU/mL (range 2.7, 7.3). SVR12 was achieved in 97% (29/30; early discontinuation at week 2, n = 1; per protocol 100%, 29/29). No relapse or reinfection was observed. In conclusion, paritaprevir/ritonavir/ombitasvir and dasabuvir (with ribavirin) for eight weeks were highly effective among HIV‐positive and HIV‐negative individuals with recent HCV infection. These data support the use of this shortened duration direct‐acting antiviral regimen in this population.